PEMBINAAN PERILAKU MAHASISWA PENDIDIKAN BIOLOGI DALAM MEMINIMALISASI SAMPAH PLASTIK DI KAMPUS UNIVERSITAS ABULYATAMA MELALUI PENGGUNAAN REUSABLE BOTTLE UNTUK KEBUTUHAN AIR MINUMNYA - Zamzami Zamzami; Helman Saputra (Jurnal Dedikasi Pendidikan, 2021)
The use of drinking water in plastic packaging is very high in the community, including in the Abulyatama University cafeteria. This happens because the behavior of everyone does not want to be a bother and has the ability to buy it. Such habits will have an impact on the production of very high plastic waste in the environment. Research on developing the behavior of biology education students in minimizing plastic waste on the Abulyatama University through the use of reusable bottles for their drinking water needs was carried out in March 2020. The research aims to determine the level of knowledge and behavior of biology education students in an effort to minimize plastic waste on the Abulyatama University. With the use of a reusable bottle for drinking water needs. The research subjects were all students of Abulyatama University Biology Education, 32 students. The method used is a survey method with the research instrument was a questionnaire. The results showed that students' knowledge of plastic and its problems were in good category (average percentage 68), students’ behavior in using reusable bottles for their drinking water needs were in good category (average percentage 67), and there was a correspondence between student knowledge and behavior. In minimizing plastic waste on the Abulyatama University Campus by using reusable bottles for drinking water needs.